Authority of Spiritual Leadership at Pesantren Temboro Based on Jamaah Tabligh Ideology - Arifin, Zainal (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2017)
Kiai is a charismatic figure who has an influence on the existence of pesantren. Spiritual leadership is a typology of Kiai based on the values of Islamic spirituality. This study examines the source of authority of the spiritual leadership of the Kiai using the perspective of Weber's authority theory. Using the approach of religious phenomenology, this study observes phenomenologically the spiritual leadership of Kiai at Pesantren al-Fatah (or known as Pesantren Temboro), which became the center of the biggest ideology ofJamaah Tabligh in Southeast Asia. Research data was obtained through in-depth interviews, active participation, documentation, and open questionnaires. This research found the three authorities of spiritual leadership at Pesantren Temboro, namely traditional, charismatic, and rational. First, traditional authority derives from three traditions: (1) pesantren education, (2) Jamaah Tabligh, and (3) the NaqsyabandiyahKhalidiyahcongregation. Second, charismatic authority derives from the spiritual qualities of the Kiai and is reinforced by karomah. Third, rational authority derives from the rational efforts of Kiai in opening formal madrasah as a form of modernization in Islamic educational institutions.